Kecerdasan Emosional dan Komitmen Kerja Dalam Mempengaruhi Kinerja Karyawan di IT Clinic Cabang Kediri - Indah Yuni Astuti (Universitas Islam Kadiri, 2021)
This study discusses human resource management regarding Emotional Intelligence and Work Commitments and Employee Performance conducted, this research period in May 2020 to July 2020 with a total sample of 32 employees and the sampling technique using purposive sampling using criteria that the employee service period is over 5 years and consistent with work which he lived. The analysis technique used is the validity and reliability test, the classic assumption test, multiple linear regression test, R2 test, t test and F test. The results of research conducted can be explained that partially there is an influence between Emotional Intelligence (X1) on Employee Performance (Y). Partially there is an influence between Work Commitment (X1) on Employee Performance (Y). Emotional Intelligence (X1) and Work Commitment (X2) simultaneously affect Employee Performance (Y). Based on these results the company management is advised to pay attention to employee potential through attitudes and character in carrying out its performance, by providing knowledge and understanding of managing emotional psychology while working and maintaining its commitment to the company.